Page from a magazine with scenes from the funeral of Walther Rathenau. Top, left: president Ebert leaves the Reichstag with general Von Seeckt and the american ambassador Houghton
Page from a magazine with scenes from the funeral of Walther Rathenau. Top, left: president Ebert leaves the Reichstag with general Von Seeckt and the american ambassador Houghton.